Desenvolvimento de microcápsulas contendo Lactobacillus acidophilus e óleo de chia (Salvia hispânica l) pela técnica de gelificação iônica externa - Pinto, Vandré Sonza (2023)
The growth in consumer demand and interest in food products with potential health benefits has encouraged research into the development of functional foods. Among these, probiotics stand out for their role in regulating the intestinal system. There are also polyunsaturated fatty acids, especially those belonging to the omega group, the most popular of which is omega-3. However, factors such as storage at low temperatures, acidity, the presence of light and degradation during passage through the human digestive system affect the viability of these microorganisms as well as their lipid stability. This makes it necessary to use new technologies to protect these substances. Microencapsulation has emerged as an alternative for the preservation of probiotics and lipid substances, as well as for their controlled release. The aim of this study was to develop microparticles using the external ionic gelation technique. Alginate (2%) was used as the wall material and emulsified with chia oil (Salvia hispanica L.) at concentrations of 10%, 15% and 20%, both containing Lactobacillus acidophilus- LA02. The size and distribution of the microparticles, the encapsulation efficiency of the microorganism and the oil, viability in gastrointestinal simulation, stability of the bacteria and lipid during different storage conditions (25, 7 and -18 °C) for 90 days, monitoring of the lipid profile for 90 days and resistance of the microparticles to heat treatment (72 °C / 15 s and 63 °C / 30 min) were analyzed. The microparticles varied in size from 206 - 363 μm. The microparticles with probiotic and oil protected the microorganisms in the tests to evaluate simulated gastrointestinal resistance and heat treatment. As for storage at 25ºC and 7ºC, the treatments containing the oil kept the probiotics viable for 90 days. The microparticles also protected the probiotics and the oil from oxidation at the storage temperatures, with -18°C and 7°C having the best performances in terms of oxidative control. Finally, based on the results obtained, it can be concluded that the co-encapsulation of Lactobacillus acidophilus and chia oil was successfully achieved and is an alternative to enable the protection of both substances in food.